If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x+9)=-50+74
We move all terms to the left:
4(3x+9)-(-50+74)=0
We add all the numbers together, and all the variables
4(3x+9)-24=0
We multiply parentheses
12x+36-24=0
We add all the numbers together, and all the variables
12x+12=0
We move all terms containing x to the left, all other terms to the right
12x=-12
x=-12/12
x=-1
| 3y+11=y-3 | | -5=-2-d | | 5a+8=2a+41 | | 2y-3(2-y)=10 | | 4w-23=8w-7 | | 40+4x=5(-x+2)-42 | | (x/4)+7=-9 | | 3x+27–3=2x+x+30-6 | | X^-2x=146 | | -5(-4x-5)=-14 | | 0=∛x | | 3(8x-1)-5x=5 | | w+49+90=180 | | 17.8=5n-2 | | (4x+29)=(12x+55)=180 | | 3x+2x+43=180 | | 5 | | 13j-6j-5j=12 | | 4x+1/x+1=12/x^2-1+3 | | 6(-8x-3)-2x=4 | | 4x+3=119 | | 0=x^2+51x | | 5 | | 0=x2+51x | | (3x+11)+25=90 | | x=2+2.6/5 | | 8n-2n-4n-2n+n=19 | | v=9+2v | | -5(-3x-4)-2x-5=-3 | | 5a−7=5+a | | Y=3√x | | 0.45(3.17+1.6)+5x=18 |